Bird-Self Accumulated. - Judson, Don (NYU Press, 1996)
"When BooBoo stabs Morris Boyle I am reading a news magazine that someone has smuggled into the wing.". Thus, the protagonist of this novella introduces us to prison, one of the several worlds he inhabits, worlds most of us would rather ignore but which inexorably, through what we see and hear and read and live on uncountable American streets, has become the one world we can no longer avoid. It seduces us with the voice of drugs and violence. Of the disenfranchised. Of those both at once outside and standing within the center of what no longer holds. It informs us of who we are today.